1982
DOI: 10.1007/bf00987783
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone chemistry of the western spruce budwormChoristoneura occidentalis Free

Abstract: SCOT capillary Chromatographic and SCOT capillary chromatographic-mass spectrometic analyses of gland washes and effluvia of virgin femaleChoristoneura occidentalis Free, have been conducted with both a diapausing and nondiapausing strain of this insect. The following compounds were identified in gland washes and effluvia in both strains:E andZ11-14∶Ald,E andZ11-14∶Ac,E andZ11-14∶OH and 14∶Ald, 14∶Ac, and 14∶OH. The average aldehyde: acetate: alcohol ratio found by analysis of single glands by virgin females (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The addition of 1:O. Silk et al (1982) reported that females of C. occidentalis release TDALs, TDACs, and TDOLs in a ratio of 10:3:8 but Cory et al (1982), using a different technique, found that C. occidentalis released TDALs and TDACs in a 98:2 ratio but did not release TDOLs in a detectable quantity. This supports the findings of Cory et al (1982) that addition of TDACs and TDOLs did not affect attraction of C. occidentalis to TDALs in south-central British Columbia and south-central Oregon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of 1:O. Silk et al (1982) reported that females of C. occidentalis release TDALs, TDACs, and TDOLs in a ratio of 10:3:8 but Cory et al (1982), using a different technique, found that C. occidentalis released TDALs and TDACs in a 98:2 ratio but did not release TDOLs in a detectable quantity. This supports the findings of Cory et al (1982) that addition of TDACs and TDOLs did not affect attraction of C. occidentalis to TDALs in south-central British Columbia and south-central Oregon.…”
Section: Discussionmentioning
confidence: 99%
“…All dosages are given as proportions of the average natural release rate of TDALs from 1 female C. occidentalis (3 nglh (Cory et al 1982;Silk et al 1982)). Baits were prepared by applying a 100-pL dichloromethane solution of pheromone components to red rubber septa (#8753-D22, Arthur H. Thomas, Philadelphia, PA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in June and July of 1962. Subsequent studies (Sanders et al 1974;Sanders and Weatherston 1976;Cory et al 1982;Silk et al 1982) showed that female C . and Alaska.…”
Section: Introductionmentioning
confidence: 99%
“…A number of insect pests of Canadian forests use different ratios of these aldehydes as part of their pheromone blends (see Discussion), the most important being the spruce budworm, February 1983 Choristoneura fumiferana (Sanders and Weatherston 1976;Silk et al 1980), the westem budworm, C . occidentalis (Silk et al 1982), and the oak leaf shredder, Croesia semipurpurana (Grant et al 1981;Weatherston et al 1978). Thus another reason for identifying the sex pheromone of the maple leaf roller was to provide additional information on species that are attracted to pheromone monitoring traps baited with these aldehydes.…”
Section: Introductionmentioning
confidence: 99%